Early Screening Tool For Autism Spectrum Disorder For Visual Impairments - Che Ku Mohd, Che Ku Nuraini; Rosli, Zareena; Suparjoh, Suriawati; Shahbodin, Faaizah (Asian Research Publishing Network (ARPN), 2019)
The aim of the present study was to evaluate developed screening tools on autism students’ to detect early signs especially on visual for ASD children. Early intervention in autism spectrum disorder (ASD) improves outcomes, but treatment access depends on early identification. Method of collecting data was using tool, observation and interview. Design stage produces flowchart and storyboard and development stage produces learning media with conceptual characteristics presented through materials equipped with visualization in the form of videos, pictures, sound and text. The results of this research illustrate that there is a positive score and feedback from children with autism. Besides that, children with autism are easy to focus using this tool. Recommendation of a screening for autism disorders in practice when concerns from parents or family are not raised, challenge the quality of the instrument and the overall screening procedure. The benefits of early ASD screening and detection must be weighed against the risk for false positive test results causingparents unnecessary worry.